Optimal Treatment Method for Prurigo Patients with Neuropsychic Features (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Given the problematic nature of comorbid disorders especially if patients with prurigo and neuropsychiatric disorders, the article considers the possibility of using tranquilizers for the treatment of prurigo. And also for local treatment the use of tincture of chilli pepper in long-term treatment purposes, which will save money ball.